Effectiveness of deep tissue massage therapy, and supervised strengthening and stretching exercises for subacute or persistent disabling neck pain. The Stockholm Neck (STONE) randomized controlled trial. (February 2020) - Skillgate, Eva; Pico-Espinosa, Oscar Javier; Côté, Pierre; Jensen, Irene; Viklund, Peter; Bottai, Matteo; Holm, Lena W.
Abstract: Objective: To compare the effectiveness of deep tissue massage, supervised strengthening and stretching exercises, and a combined therapy (exercise followed by massage) (index groups), with advice to stay active (control group). Methods: Randomized controlled trial of 619 adults with subacute or persistent neck pain allocated to massage (n = 145), exercise (n = 160), combined therapy (n = 169) or advice (n = 147). Primary outcomes were minimal clinically important improvements in neck pain intensity and pain-related disability based on adapted questions from the Chronic Pain Questionnaire. Secondary outcomes were perceived recovery and sickness absence. Outcomes were measured at seven, 12, 26 and 52 weeks. Results: We found improvement in pain intensity favouring massage and combined therapy compared to advice; at seven weeks (RR = 1.36; 95%CI:1.04–1.77) and 26 weeks (RR = 1.23; 95%CI:0.97–1.56); and seven (RR = 1.39; 95%CI:1.08–1.81) and 12 weeks (RR = 1.28; 95%CI:1.02–1.60) respectively, but not at later follow-ups. Exercise showed higher improvement of pain intensity at 26 weeks (RR = 1.31; 95%CI:1.04–1.65). Perceived recovery was higher in the index groups than in the advice group at all follow-ups. We found no consistent differences in pain related disability or sickness absence. Conclusions: In this study, at 12-months follow-up, none of the index therapies were more effective than advice in terms of pain intensity in the long term or in terms of pain-related disability in the short or long term. However, the index therapies led to higher incidence of improvement in pain intensity in the short term, and higher incidence of favorable perceived recovery in the short and in the long term than advice. Trial registration: ISRCTN01453590. Registered 3 July 2014. Highlights: Massage is more effective than advice for pain intensity in the short term. Exercises are more effective than advice for pain intensity in the short term. Combined therapy is more effective than advice for pain intensity in the short term. These interventions are not more effective than advice in reducing pain-related disability. These interventions are more effective than advice in improving perceived recovery.